STUDENTS’ PERCEPTION TOWARD THE USE OF PADLET TO IMPROVE THEIR WRITING SKILLS - Aslam, Alfian Abiyyu; Puspita, Shelley Salsabila Nanda; Hariyana, Salsabila Zahrah (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
The use of digital technologies such as applications and websites can be seen at almost every level of education today. However, the main problem in pursuing the goal of teaching English is the imbalance between the material being taught and the time to teach the material. In the English language, there are certain skills that need to be mastered, particularly in the area of writing.   One important aspect of writing skills is the ability to compose report texts, which is deemed essential for students. The primary objective of this article is to explore how students perceive the use of Padlet as a tool to enhance their report writing skills. The research methodology employed for this study is descriptive qualitative in nature. The qualitative information gathered from a survey conducted among students regarding their opinions on using Padlet for improving writing skills was analyzed. Questionnaires and interview guidelines served as the research tools. The questionnaire results were analysed in terms of percentages and then combined with insights from the interviews to create narrative summaries. The participants exhibited positive attitudes towards utilizing Padlet for writing report texts. Additionally, they highlighted the opportunities that Padlet offers for students to enhance their English skills, particularly in collaborative writing activities.